Blood Plasma Separation: Enhanced Diamagnetic Repulsion of Blood Cells Enables Versatile Plasma Separation for Biomarker Analysis in Blood (Small 23/2021). Issue 23 (10th June 2021) - Kwon, Seyong; Oh, Jieung; Lee, Min Seok; Um, Eujin; Jeong, Joonwoo; Kang, Joo H.
Abstract : In article 2100797, Joo H. Kang, and co‐authors present a new blood plasma extraction device using augmented diamagnetic repulsion of blood cells by supplementing superparamagnetic iron oxide nanoparticles to whole blood and demonstrate its utility for various biomarker analysis, such as prostate‐specific antigen, platelets, exosomes, and nucleic acids, in whole blood without prior blood plasma separation.